Edukasi dan Pelatihan Pembuatan Turunan Hasil Olahan dari Produk Lebah Kelulut pada Kelompok Peternak Lebah di Samarinda: Education and Training on Making Derivatives from Kelulut Bee Products for Beekeepers in Samarinda - Paula Mariana Kustiawan; Deasy Nur Chairin Hanifa; Alfin Syahrian Dwi Nugraha; Ahmad Suwandi; Agnes Monica; Asmiranda Agustinur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Kelulut bee (Trigona sp.) products knowly as honey, pollen and propolis. Kelulut beekeepers in Samarinda are still oriented towards income from the sale of honey. The purpose of this activity is to improve the understanding and skills of kelulut beekeepers in making derivative products from honey as an alternative to selling value products. This community service is carried out by means of education and training in making products made from honey, propolis and pollen. The results of the evaluation of community service activities are measured by their level of understanding after being given training to have a good increase in the level of knowledge. The activity received a very good appreciation and participants hoped that the activity would be carried out regularly.